Realization of a single-Cooper-pair Josephson laser - Chen, Fei; Li, Juliang; Armour, A.D.; Brahimi, E.; Stettenheim, Joel; Sirois, A.J.; Simmonds, R.W.; Blencowe, M.P.; Rimberg, A.J. (American Physical Society, 2014)
We have embedded a voltage-biased Cooper-pair transistor (CPT) in a high-Q superconducting microwave cavity. When the energy given to a tunneling Cooper pair by the voltage bias is equal to a multiple of the cavity photon frequency, the cavity is pumped to a strongly nonequilibrium state. The cavity photons act back on the CPT, allowing us to enter a regime of strongly correlated electronic-photonic transport. We directly observe the effects of photonic backaction on Cooper-pair transport, and see clear evidence for single-emitter lasing in the form of emission dominated by stimulated transport processes.